DuPont profitability analysis of different types of agricultural farms in Croatia - Vesna OČIĆ; Zoran GRGIĆ; Branka ŠAKIĆ BOBIĆ; Kristina BATELJA LODETA; Tihana KOVAČIĆEK (Journal of Central European Agriculture, 2025)
The DuPont analysis is a useful and simple tool for measuring the financial performance of agricultural farms and assessing the company's profit potential. The research objective of this paper is to analyse eight different types of farms and two regions of the Republic of Croatia in the period from Croatia's accession to the European Union in 2013 until 2021. The data from the Standard results, which represent the weighted averages of agricultural farms in the FADN sample, were used. The Farm Accountancy Data Network (FADN) is a European data collection system with the aim of annual determination of the farm income and business analysis of the agricultural farm. It can be concluded that the profitability of agricultural farms in Croatia increased in the observed period, but with significant deviations. Return on equity (ROE) shows the earning potential of invested own capital and is the top indicator of the DuPont analysis. In both regions of the Republic of Croatia (Adriatic and Continental), a positive change can be observed after 2017, with better indicators in Continental Croatia. The lowest ROE was recorded for the mixed type in 2014, when the return on equity was -10.52%. The highest ROE (12.44%) was recorded for the milk type in 2020. For all types, as well as all regions, there are large fluctuations in return on equity caused primarily by changes in gross and net farm income.